STUDI PENERAPAN PRODUKSI BERSIH UNTUK INDUSTRI KERUPUK - Banun Diyah Probowati; Burhan Burhan (AGROINTEK, 2011)
Cleaner productionwas minimize waste and emissions and maximize product output. The aimed of research were to identified and to analysed application of cleaner production from crackers industry. By analysing the flow of materials and energy in this industry and then to identify options to minimize waste industrial processes. Improvements of organisation and technology help to reduce or suggest better choices in use of materials and energy, and to avoid waste, waste water generation, and gaseous emissions, and also waste heat.. Application of this cleaner production were a good house keeping, recycle, reduce and reuse. Modified a fireplace and smoked funnel were the choice of alternative to application the cleaner production. The benefit from application of cleaner production was 5% efficiency wood to be burn. There was the complete process of burning with value of efficiency.